Stepwise extinction of larger foraminifers at the Cenomanian-Turonian boundary: A shallow-water perspective on nutrient fluctuations during Oceanic Anoxic Event 2 (Bonarelli Event) - Parente, M; Frijia, G; Di Lucia, M; Jenkyns, H; Woodfine, R; Baroncini, F (2008)
A two-step pattern in the extinction of larger foraminifers is recorded in the upper Cenomanian shallow-water carbonates of the southern Apennines (Italy). The first step eliminated the alveolinids, the most extreme oligotrophs, and reduced dramatically the diversity of larger foraminifers. The second step wiped out the few survivors, seemingly able to tolerate mesotrophic conditions, leaving a disaster fauna dominated by small heterotrophs. This pattern of extinction parallels the ecological succession of shallow-water benthic foraminiferal assemblages along a gradient of increasing nutrient availability. High-resolution carbon isotope stratigraphy shows that the extinction of alveolinids was contemporaneous with the extinction of rotaliporid planktic foraminifers, the drowning of certain Tethyan carbonate platforms, and an episode of thermal instability recorded in sea-surface temperature in the open ocean. Ocean stratification, during the first phase of Oceanic Anoxic Event 2, would have promoted oligotrophic conditions in surface tropical waters and maximum diversity of larger foraminifers. Following this, ocean overturning caused by surface-water cooling is credited with delivering to shallow-water environments the excess nutrient loads previously stored at depth, triggering the environmental changes leading to stepwise extinction of larger foraminifers. © 2008 The Geological Society of America.